2020
DOI: 10.1016/j.stem.2019.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem and Progenitor Cells Exhibit Stage-Specific Translational Programs via mTOR- and CDK1-Dependent Mechanisms

Abstract: Highlights d HSPCs exhibit post-transcriptional and translational mechanisms of gene regulation d mTOR is targeted for proteasomal degradation in myeloid progenitors by c-Cbl d CDK1 regulates the activation of eIF4E-dependent translation in myeloid progenitors d Aberrant mTOR expression in myeloid progenitors results in increased myeloid cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…Our study identified several kinase targets of CBX family in SKCM, including PLK1 and CDK1. Interestingly, we found that these kinases were associated with genomic stability, mitosis, and transcription activity 32,33 . Upregulation of PLK1 could maintain chromosomal instability and inhibit the genesis and proliferation of cancers 33,34 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Our study identified several kinase targets of CBX family in SKCM, including PLK1 and CDK1. Interestingly, we found that these kinases were associated with genomic stability, mitosis, and transcription activity 32,33 . Upregulation of PLK1 could maintain chromosomal instability and inhibit the genesis and proliferation of cancers 33,34 .…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, we found that these kinases were associated with genomic stability, mitosis, and transcription activity. 32,33 Upregulation of PLK1 could maintain chromosomal instability and inhibit the genesis and proliferation of cancers. 33,34 PLK1 alteration could facilitate cancerous transformation and promote cancer development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was recently shown that differentiation of HSCs in myeloid progenitors requires not only a general increase in protein synthesis but also the translation of specific mRNAs [ 13 ]. Importantly, the alteration in ribosome levels that accompanies cell development can affect not only global protein synthesis but also the translation of specific transcripts.…”
Section: Balanced Ribosome Biogenesis and Translation Are Important For Hematopoietic Developmentmentioning
confidence: 99%
“…However, within the epitranscriptome, modifications present in rRNAs and tRNAs largely prevail. Hematopoietic development requires tight control of protein synthesis [ 12 , 13 ]. Furthermore, translational deregulation strongly contributes to hematopoietic malignancies [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%